Micromorphological observation of seed coat of Eucalyptus species (Myrtaceae) using scanning electron microscopy technique. Issue 2 (23rd October 2018) - Luqman, Muhammad; Zafar, Muhammad; Ahmad, Mushtaq; Ozturk, Munir; Sultana, Shazia; Alam, Fakhre; Ullah, Farhat
Abstract: Seed shape, surface cells shape, arrangement, anticlinal wall pattern, and periclinal wall protuberances were recorded for nine species of Eucalyptus (Myrtaceae) using scanning electron microscopy to determine the importance of seed morphological characters as an additional tool for identification. Most of the seeds were found ovate and some seeds were elliptic and cuboid in shape. Almost reticulate regular seed surface patterns were observed. Four types of surface cells were examined; diamond, elliptic, oblong, and irregular. Majority of the seeds showed raised anticlinal wall level and diversity from wavy to puzzle in pattern. Periclinal wall may be glabrous or having protuberances that were rhombus and bullate in shape. Both macro‐ and micromorphological characters can provide basis for classification and delimitation of genus Eucalyptus . Research highlights: Seeds quantitative characters of nine Eucalyptus species as seed length, width, and weight. Macromorphological characters of seeds including seed color, helium position, and seed shape. Micromorphological characters include seed surface, periclinal wall, and anticlinal wall investigation under scanning electron microscope. Ultra‐seed sculpturing features as an additional tool in identification. Abstract :